Physical activity and effectiveness of the McKenzie method in patients with lumbar spine pain syndrome - Grzegorz Olkowski; Jan Ślężyński (Medycyna Ogólna i Nauki o Zdrowiu, 2021)
Introduction The study concerns patients with lumbar spine pain syndrome who had undergone therapy by the McKenzie method.